2014
DOI: 10.1097/cmr.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Novel somatic KIT exon 8 mutation with dramatic response to imatinib in a patient with mucosal melanoma

Abstract: Primary mucosal melanomas represent ∼1.3% of all cases of melanoma diagnosed in the USA. The sinonasal location is the most common primary site. Mutations in the KIT gene occur in 10-22% of mucosal melanomas. Tumor response to imatinib mesylate has been reported in about half of the patients with tumors harboring KIT mutations. Responses are almost exclusively restricted to tumors with mutations in KIT exon 9 or 11. We report a case of a patient with a sinonasal mucosal melanoma with a novel exon 8 mutation (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While mutational status did not confer prognostic value in our study, perhaps the value of mutational analysis likely resides in future attempts at therapy targeted at these pathways. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mutational status did not confer prognostic value in our study, perhaps the value of mutational analysis likely resides in future attempts at therapy targeted at these pathways. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Although mutational status did not confer prognostic value in our study, perhaps the value of mutational analysis likely resides in future attempts at therapy targeted at these pathways. 27 The role of RT has remained controversial for sinonasal mucosal melanoma. Eighty-two percent of patients (64/ 78) with localized sinonasal mucosal melanoma at MSKCC received adjuvant or definitive RT after surgery, consistent with common practice based on retrospective series.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it was reported that melanoma non-responders harbor specific c-KIT mutations known to confer imatinib resistance in GIST, such as D820Y, N822K, and A829P, while responders show mutation on exon 11 or exon 13 [31,32]. In 2014, a case report expanded the melanoma population that could benefit from imatinib to those with somatic exon 8 KIT mutations [46].…”
Section: Imatinib (Gleevec ® )mentioning
confidence: 99%
“…Similar results were achieved by Amit et al and Chraybi et al [ 26 , 27 ], who reported that these mutations could be used for direct targeted therapy. Targeted therapy has provided promising results in the treatment of SNMM [ 23 , 28 ]. Cao et al recently reported that an SNMM patient with a ROS1 fusion achieved complete remission after 8 months of treatment with crizotinib [ 29 ].…”
Section: Discussionmentioning
confidence: 99%